2020
DOI: 10.1111/cge.13735
|View full text |Cite
|
Sign up to set email alerts
|

B4GALT1‐congenital disorders of glycosylation: Expansion of the phenotypic and molecular spectrum and review of the literature

Abstract: A congenital disorder of glycosylation due to biallelic mutations in B4GALT1 has been previously reported in only three patients with two different mutations. Through homozygosity mapping followed by segregation analysis in an extended pedigree, we identified three additional patients homozygous for a novel mutation in B4GALT1, expanding the phenotypic spectrum of the disease. The patients showed a uniform clinical presentation with intellectual disability, marked pancytopenia requiring chronic management, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A rare homozygous frame shift insertion in B4GALT1 that predicts a nonfunctional truncated protein was reported to cause congenital disorder of glycosylation type 2 (CDGII) (28)(29)(30)(31). Three of the six reported CDGII patients exhibited, among other traits, abnormal coagulation and very high levels of aspartate transaminase (AST).…”
Section: Association Analyses Identify B4galt1 Pasn352ser As a New Ld...mentioning
confidence: 99%
“…A rare homozygous frame shift insertion in B4GALT1 that predicts a nonfunctional truncated protein was reported to cause congenital disorder of glycosylation type 2 (CDGII) (28)(29)(30)(31). Three of the six reported CDGII patients exhibited, among other traits, abnormal coagulation and very high levels of aspartate transaminase (AST).…”
Section: Association Analyses Identify B4galt1 Pasn352ser As a New Ld...mentioning
confidence: 99%
“…A similar N-glycoprofile was detected in B4GALT1-CDG with the presence of increased levels of truncated glycans with terminal N-acetylhexosamines (Hex3HexNAc4, Hex3HexNAc5, Hex3HexNAc5Fuc1) and bi-antennary glycans missing both galactose and sialic acid moieties (Hex4HexNAc4NeuAc1). The difference between B4GALT1-CDG and SLC35A2-CDG lies mainly in the elevated level of Hex3HexNAc4Fuc1 glycan in B4GALT1-CDG [33,34], which was not observed in increased relative intensity in either presented or previously identified SLC35A2-CDG patients. An increase in several complex truncated glycans lacking galactose and sialic acid was reported in TMEM165-CDG [35][36][37]; however, neither the serum nor Tf N-glycoprofile of SLC35A2-CDG patients reveals increased levels of monosialylated biantennary glycans with two galactoses (Hex5HexNAc4NeuAc1 ± Fuc1) which were identified in TMEM165-CDG.…”
Section: Discussionmentioning
confidence: 65%
“…Staretz-Chacham et al described three additional patients homozygous for a novel mutation in β4GALT1 (p.Arg21Trp), located within its transmembrane domain. These patients showed a uniform clinical presentation with intellectual disability, profound pancytopenia requiring chronic treatment, and novel features including pulmonary hypertension and nephrotic syndrome [ 60 ]. In addition, Giannini et al generated a B4galt1 -/- mouse and observed that β4GALT1 deficiency increases the number of differentiated MKs.…”
Section: Disorders Of Glycosylation Associate With Syndromic Thromboc...mentioning
confidence: 99%